NATURAL FORMATION OF THE UNIVERSE AND ASTRONOMY - Bagas Ilham Yudhiyantoro; Anniza Rahayu Hadiyanto; Nurrafiza Nurrafiza (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2022)
In the natural formation of universe , exists a number of theory from the west that says universe is made from big bang. However, not only theory from the west but in the Qur’an also has explained how the formation of the universe happened. Before we learn about the universe, we have to study astronomy. It is because naturalformation and astronomy are related each other. In the western theory, earth is located among many galaxies in the solar system. Earth is the most fertile plenet because on earth there are numerous living things. The aim of this study is to know natural formation of the universe according to western theory, Islamic religious teachings and astronomy. This study used library research method. Research finding shows that western theory has three theories natural formation of theuniverse, they are the Big Bang Theory, the Oscillating Theory and Steady-state. According to Astronomy there are three theories, they are Egocentric theory, Geocentric theory and Heliocentric theory. In Islamic religious teachings,the formation of earth occur During six phase /time with gradual creation .